Influence of socioeconomic factors on female entrepreneurship: an analysis using structural equation modeling (PLS-SEM) - Bazán Valque, Rosa Ysabel; Cruz Caro, Omer; Portilla Bazán, William Humberto; Torres Armas, Elías Alberto; Samillan Vasquez, Cesar Jefferson; Rojas Puerta, Carlos Andres (Frontiers in Sociology, 2025)
Female entrepreneurship has emerged as a strategy for reducing poverty, generating employment opportunities, and promoting gender equality, particularly in rural areas where structural inequalities persist. However, there is still a limited understanding of how socioeconomic factors influence their development. This study aimed to analyze the influence of these factors on women-led entrepreneurship, considering dimensions such as family income, social empowerment, economic growth, access to resources, entrepreneurial capabilities, and sociocultural factors. The research was conducted with a sample of 98 female entrepreneurs from the province of Chachapoyas, Amazonas region of Peru, providing context-specific evidence for understanding female entrepreneurship in a rural Amazonian setting rarely studied. The initial least squares structural equation modeling (PLS-SEM) technique was employed, supported by SmartPLS4 software. The results indicate that socioeconomic factors have a positive impact on income, empowerment, and economic growth. Furthermore, female entrepreneurship strengthens capacities, facilitates access to productive resources, and contributes to transforming restrictive cultural norms. Beyond the financial benefits, it acts as a driver of social change. This study offers a comprehensive framework for understanding female entrepreneurship. It provides useful evidence for the design of public policies promoting women's economic inclusion in historically excluded areas.